The Role of Education Against Bullying Cases in Indonesia - Neng Nur Annisa; Dimas Sakti Aprilianto; Maulana Suhandani; Maya Putri Jayanti (Khazanah Pendidikan Islam, 2022)
The act of bullying is an attempt by an individual or group to suppress someone with the aim that the person being bullied feels hurt either mentally or physically and this is very dangerous, of course, because if the act of bullying has reached an extreme level, the result is that the victim being bullied can stress to commit suicide, and it's no secret that the school environment is one of the places where bullying often occurs. This study uses qualitative data collection techniques with a content approach. The data from the research results that we collected based on the Google form platform that we used, among others, obtained as many as 32 respondents in this bullying case study. In the results of our research we found various kinds of problems that respondents had experienced related to bullying starting from the form of bullying treatment in 4 forms namely Physical, Cyber, Mental and Verbal, then how did they respond to the bullying they had experienced to the role in the environment around the respondents in overcoming and overcome the problem of bullying.